2020
DOI: 10.1111/jeb.13727
|View full text |Cite
|
Sign up to set email alerts
|

microRNA expression variation as a potential molecular mechanism contributing to adaptation to hydrogen sulphide

Abstract: microRNAs (miRNAs) are post‐transcriptional regulators of gene expression and can play an important role in modulating organismal development and physiology in response to environmental stress. However, the role of miRNAs in mediating adaptation to diverse environments in natural study systems remains largely unexplored. Here, we characterized miRNAs and their expression in Poecilia mexicana, a species of small fish that inhabits both normal streams and extreme environments in the form of springs rich in toxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 92 publications
0
15
0
Order By: Relevance
“…We have previously shown that P. mexicana from sulfidic populations can survive in high levels of H 2 S by constitutively expressing high levels of important H 2 S detoxification genes (40)(41)(42), and some sulfidic populations have evolved a resistant cytochrome c oxidase (43). Moreover, there is heritable variation in gene expression, especially in key genes related to H 2 S toxicity and detoxification (44), some of which may be driven by expression differences of relevant microRNAs (45). Despite these observations, a key gap in our knowledge is the effect of H 2 S exposure on epigenetics and whether expression changes due to H 2 S exposure and local adaptation are potentially mediated by DNA methylation changes.…”
mentioning
confidence: 99%
“…We have previously shown that P. mexicana from sulfidic populations can survive in high levels of H 2 S by constitutively expressing high levels of important H 2 S detoxification genes (40)(41)(42), and some sulfidic populations have evolved a resistant cytochrome c oxidase (43). Moreover, there is heritable variation in gene expression, especially in key genes related to H 2 S toxicity and detoxification (44), some of which may be driven by expression differences of relevant microRNAs (45). Despite these observations, a key gap in our knowledge is the effect of H 2 S exposure on epigenetics and whether expression changes due to H 2 S exposure and local adaptation are potentially mediated by DNA methylation changes.…”
mentioning
confidence: 99%
“…[31], which was first run using the rainbow trout reference genome (NCBI RefSeq assembly accession GCF_002163495.1) and all ovarian fluid and plasma reads generated in the present study. This was performed using a set of five manually curated fish mature and hairpin sequences ( Lepisosteus oculatus, Danio rero , Poecilia Mexicana, Gasterosteus aculeatus , and Chaenocephalus aceratus ) [30,32,33]. Prost!…”
Section: Methodsmentioning
confidence: 99%
“…These regions of DNA methylation were related to various cellular activities ranging from signaling to apoptosis, and sulfur metabolism. These methylated regions showed a high degree of overlap across generations, suggesting DNA methylation as a possible epigenetic mechanism for this heritable adaptive phenotype [35].…”
Section: Dna Methylationmentioning
confidence: 99%